Peningkatan Perekonomian Komunitas Difabel Gumregah Yogyakarta Melalui Pelatihan Ekonomi Kreatif - Sowanya Ardi Prahara; Nafida Hetty Marhaeni; Angelina Dyah Arum Setyaningtyas (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
The existence of persons with disabilities in Indonesia from year to year based on data from the Central Statistics Agency is increasing. The government has regulated the rights of persons with disabilities in the Law on Persons with Disabilities whose aim is to eliminate inequalities so that they have equal opportunities. But in reality, not all of their rights can be obtained, including equality in getting a job. The Gumregah Pinlih Disabled Community and its members need knowledge and skills to improve their economy and welfare. This is based on the potential of each member to develop and empower the economy. One of the opportunities is with a pastry business idea. This is based on the fact that the average person with disabilities is a woman who can be empowered to make pastries and maximize the promotion of processed products through social media, especially since this activity is carried out near the holy months of Ramadan and Idul Fitri. This training was given by the UMBY PKM Team with students of the UAD Food Service Business Study Program in conducting a demonstration of making pastries. Pastry making training and promotion of processed products through social media is very useful and motivates participants to continue it as an alternative business to improve the economy and welfare of its members